The Federal Democratic Republic of Ethiopia : Joint Staff Advisory Note of the Poverty Reduction Strategy Paper; 2003/04 Annual Progress Report. (IMF Staff Country Reports; Country Report, 2006)
This paper presents a Joint Staff Advisory Note on the Federal Democratic Republic of Ethiopia's Poverty Reduction Strategy. Excessive domestic bank financing of the budget deficit could crowd out the private sector, increase pressure on reserve and inflation targets, and, given the already high levels of domestic debt, increase vulnerability to macroeconomic shocks. Public infrastructure investment recently increased substantially despite the lack of sound cost-benefit analysis. The strong pro-poor emphasis of government expenditure is paying off in terms of improvements in education and provision of health services.